Menumbuhkan Sikap Nasionalisme Peserta Didik Melalui Ekstrakurikuler Pramuka di MAN 2 Semarang - Febri Listiarum; Nani Mediatati (UPT Publikasi Ilmiah UNISBA, 2025)
Currently, the character among the community, especially the attitude of nationalism in students, is said to be declining due to globalization. Therefore, it is important for schools to overcome these problems through activities that can foster an attitude of nationalism. This research was conducted to find out the extracurricular activity program that can foster the nationalism attitude of students at Madrasah Aliyah Negeri (MAN) 2 Semarang. This research uses descriptive qualitative methods with observation and interview techniques. After the data were collected, the data were processed and analyzed descriptively using data triangulation techniques. The results of the research show that the scout extracurricular activity program is capable of fostering a nationalist attitude in accordance with the eight characteristics of a nationalist attitude, including: (1) welcoming guest camps; (2) exploring the terrain; (3) providing scouting materials; (4) repling; (5) PERSAMI or Saturday and Sunday Camp; (6) social service; (7) mountain climbing; and (8) PERATA or End of Year Camp.